2020
DOI: 10.3390/biom10060933
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Plasma Modulates miRNA Expression by Sow Genital Tract Lining Explants

Abstract: The seminal plasma (SP) modulates the female reproductive immune environment after mating, and microRNAs (miRNAs) could participate in the process. Considering that the boar ejaculate is built by fractions differing in SP-composition, this study evaluated whether exposure of mucosal explants of the sow internal genital tract (uterus, utero-tubal junction and isthmus) to different SP-fractions changed the profile of explant-secreted miRNAs. Mucosal explants retrieved from oestrus sows (n = 3) were in vitro expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…As mentioned above, the SP EVs have demonstrated capacity to bind to and even fuse with the sperm plasma membrane to deliver their cargo [ 76 , 138 , 176 , 177 ], influencing sperm function [ 142 , 143 , 144 ], but also via proteins such as CD59, to protect spermatozoa from responses by the immune system [ 135 ]. SP EVs have also proven, as did other EVs [ 178 ], to influence the local immunity of the female internal tract [ 179 ], and to induce inflammatory and immune responses by pig uterine cells [ 4 , 38 , 180 ]. Whether the changes in immune-related genes we have detected in peri-ovulatory sows following mating or AI, with selected ejaculate fractions (particularly the sperm-peak portion) or their sperm-free SP [ 29 ], or even in sows having pre-implantation embryos [ 173 ], are conveyed mainly by free molecules, by SP-EVs or it is the effect of a concerted signaling, remains to be experimentally tested.…”
Section: The Particulate Seminal Plasma: the Most Relevant Component Of Seminal Plasma?mentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the SP EVs have demonstrated capacity to bind to and even fuse with the sperm plasma membrane to deliver their cargo [ 76 , 138 , 176 , 177 ], influencing sperm function [ 142 , 143 , 144 ], but also via proteins such as CD59, to protect spermatozoa from responses by the immune system [ 135 ]. SP EVs have also proven, as did other EVs [ 178 ], to influence the local immunity of the female internal tract [ 179 ], and to induce inflammatory and immune responses by pig uterine cells [ 4 , 38 , 180 ]. Whether the changes in immune-related genes we have detected in peri-ovulatory sows following mating or AI, with selected ejaculate fractions (particularly the sperm-peak portion) or their sperm-free SP [ 29 ], or even in sows having pre-implantation embryos [ 173 ], are conveyed mainly by free molecules, by SP-EVs or it is the effect of a concerted signaling, remains to be experimentally tested.…”
Section: The Particulate Seminal Plasma: the Most Relevant Component Of Seminal Plasma?mentioning
confidence: 99%
“…So, what could these miRNAs rule that impacts fertility? As already mentioned, SP has the capability of eliciting inflammatory and long-lasting immune signaling by the female genital tract [ 27 , 29 , 117 , 173 ], being even able to cause release of miRNAs from the lining epithelia [ 180 ]. Responses from the female can be issued by spermatozoa alone [ 198 ] or even by the act of copulation [ 199 ], but the evidence is that these changes are rather modest, compared to what the SP can elicit, either alone or as semen (i.e., including the suspended spermatozoa).…”
Section: The Particulate Seminal Plasma: the Most Relevant Component Of Seminal Plasma?mentioning
confidence: 99%
See 1 more Smart Citation
“…The seminal plasma (SP) is made-up of secretions arising from the male accessory glands, namely epididymis, seminal vesicles, and prostate. The SP is not only a medium for sperm transport, since it can modulate the female reproductive environment and immunity [ 9 ] to allow the acquisition of sperm competence [ 10 ] to influence sperm RNA content, and even embryo development, as transcriptome studies reveal [ 11 ]. In recent years, thousands of specific transcripts and proteins have been found in human seminal plasma (SP).…”
Section: Introductionmentioning
confidence: 99%
“…It plays a crucial role in sperm survival and quality. More specifically, SP influences the female reproductive environment and immunity [16], allows the acquisition of sperm competence [17], and influences the RNA content of spermatozoa and even the embryo development, as transcriptome studies have revealed [18].…”
mentioning
confidence: 99%